2018
DOI: 10.25518/1780-4507.16499
|View full text |Cite
|
Sign up to set email alerts
|

Revue des connaissances sur la micro-filière ovine laitière en Tunisie : état des lieux et perspectives de relance de la race sicilo-sarde

Abstract: Cet article est distribué suivant les termes et les conditions de la licence CC-BY (http://creativecommons.org/licenses/by/4.0/ deed.fr) Introduction. La race sicilo-sarde est la seule race ovine laitière tunisienne. Elle est à la base d'une micro-filière de production de fromages. Son effectif s'est effondré dans les années 1990 en raison de choix économiques et politiques peu favorables ainsi que d'un manque de maitrise technique des élevages, mettant la pérennité de cette filière en danger. Toutefois, des i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Bacterial counts (log 10 CFU/mL) in the milk of studied species from the Tunisian oasis region. Milk from local QFO gave in this study total solids, fat, protein, casein, and ash content comparable to those reported by El Gharbi et al(2015) for Barbarin sheep breed reared in a semiarid climate but was lower than ndings ofAloulou et al (2018) for Sicilo-Sarde ewes and those ofRouissi et al (2008) for Sicilo-Sarde and Comisane dairy sheep breeds raised in an intensive system in the extreme north of the country. The variation from the reported results could be attributed mainly to the difference in the breed, management conditions, including feeding, and environmental factors, among others.…”
supporting
confidence: 86%
“…Bacterial counts (log 10 CFU/mL) in the milk of studied species from the Tunisian oasis region. Milk from local QFO gave in this study total solids, fat, protein, casein, and ash content comparable to those reported by El Gharbi et al(2015) for Barbarin sheep breed reared in a semiarid climate but was lower than ndings ofAloulou et al (2018) for Sicilo-Sarde ewes and those ofRouissi et al (2008) for Sicilo-Sarde and Comisane dairy sheep breeds raised in an intensive system in the extreme north of the country. The variation from the reported results could be attributed mainly to the difference in the breed, management conditions, including feeding, and environmental factors, among others.…”
supporting
confidence: 86%
“…The productivity of the two breeds’ ancestors Sarda and Comisana reached 201 and 159 L/ewe/lactation, respectively [ 7 ]. Although this truncated quantitative production is explained by this breeding strategy, the milk quality of the SS and its cheese are classified within the high range of Mediterranean dairy breeds [ 9 , 10 ]. Its milk fat, protein and casein contents, on which cheese yield depends [ 9 ], were 7.49%, 6.55% and 5.16%, respectively [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…All of these cited results highlighted the excellent milk quality of the SS sheep. Despite this high quality, SS milk is limited to micro-sector cheese production mainly characterized by handmade quality yogurts and cheeses, especially the “Sicilian” cheese with a uniquely “terroir” reputation [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations